2015
DOI: 10.1002/srin.201400360
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Burden Distribution in a Blast Furnace

Abstract: Burden distribution plays an important role in achieving stable and efficient operation in a modern ironmaking blast furnace. In this process, burden materials are charged and distributed to the throat region, and further affect gas distribution and blast furnace performance. In this work, a model based on discrete element method is established. In particular, the surface properties of spherical particles are first justified in terms of angle of repose aiming to reflect the effect of particle shape. The proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Recently, DEM 8) has been developed for the powerful simulation tool for analyzing particle behavior, and applied to simulate and visualize particle flow in the blast furnace top charging system. [9][10][11][12][13][14] The authors have already reported its high potential to be an optimizing tool for burden distribution control. Therefore, this simulation can clarify the circumferential imbalance of the particle trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DEM 8) has been developed for the powerful simulation tool for analyzing particle behavior, and applied to simulate and visualize particle flow in the blast furnace top charging system. [9][10][11][12][13][14] The authors have already reported its high potential to be an optimizing tool for burden distribution control. Therefore, this simulation can clarify the circumferential imbalance of the particle trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, such prediction has mainly relied on the models derived from the motion of a single particle or particle assembly . In recent years, the DEM approach, which considers all individual particles and their interaction with each other, has become a promising tool to guide burden charging operation …”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%
“…Such capability is, however, difficult to achieve by single particle based models . For example, the formulation of coke layers, although complicated, can be well predicted by the DEM simulations simply based on spherical particles if the friction coefficients are carefully chosen, as demonstrated in the work of Liu et al (see Fig. )Those investigators also examined the influence of sliding and rolling friction coefficients in the DEM modeling of burden charging process against the measurements.…”
Section: Modeling and Simulation Of Different Bf Regionsmentioning
confidence: 99%
“…and shaft furnace including falling trajectory, [7][8][9][10][11][12] burden profile, [13][14][15] burden pile structure [16][17][18][19] and the descent of burden layer, 20,21) only a few studies were dedicated to the burden distribution in the MG to achieve reasonable gas flow, mainly due to the short history of the process and limited experimental techniques. [22][23][24][25][26][27][28][29] Several numerical studies on the COREX MG were conducted.…”
Section: Experimental Study Of the Effects Of Operation Conditions Onmentioning
confidence: 99%